A Psychological Journey Of Optimistic/Pessimistic Cycle In The Fault In Our Stars - Muntazar Mehdi (University of Chitral Journal of Linguistics and Literature, 2019)
This paper attempts to explore the presence of Freud’s psychoanalytical tools- id, ego and superego and their role in determining the protagonists’ optimistic/pessimistic cycle towards life. The researcher has applied Psychoanalysis theory of Sigmund Freud to analyse the novel. The research has successfully revealed application of Freudian psychoanalytical tools. Moreover, the researcher has also unveiled the psychological drives which were evident during the optimistic/pessimistic cycle of protagonists’ lives. The researcher hasconcluded her research on the ground which illustrates when protagonists were having positive approach towards life, the working of superego in their life was indicated and while having pessimistic approach in their life witnessed the presence of id.